PENALARAN ASOSIATIF DAN DISOSIATIF DALAM DEBAT POLITIK DI TELEVISI - Mohamad Jazeri (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2012)
This study aims to explain the associative and dissociative reasoning in politicaldebates. The data sources were communication events in the political debates emerging inthe reform era, before the 2009 general election. The data were analyzed using a qualitativedata analysis adopted from Miles and Huberman. The fi ndings show that associativereasoning includes quasi-logic, analogy, generalization, causality, and co-existence.Dissociative reasoning includes policy and ideological dissociation. The diff erence inperspectives results in the diff erence in the ways of looking at political issues and debatecomplexity. Reasoning in political debates has two objectives, namely rationality to produce sound arguments and institutional interests to achieve a political agenda.